References for left main stem dimensions: A cross sectional intravascular ultrasound analysis. Issue 2 (27th September 2018) - van Zandvoort, Laurens J. C.; Tovar Forero, Maria N.; Masdjedi, Kaneshka; Lemmert, Miguel E.; Diletti, Roberto; Wilschut, Jeroen; de Jaegere, Peter; Zijlstra, Felix; Van Mieghem, Nicolas M.; Daemen, Joost
Abstract: Background: Angiographic assessment of left main coronary artery (LMCA) lesions remains challenging and limited data is available on reference diameters and length of nonobstructive LMCA dimensions. Our aim was to provide insights in the dimensions of nonobstructive LMCA and to find a possible correlation with gender and patient habitus. Methods: This retrospective single center study was performed in a consecutive cohort of patients who underwent Intravascular Ultrasound (IVUS) guided percutaneous coronary interventions of the left coronary system including complete pullbacks of a non‐obstructive LMCA ( n = 254). Results: Mean LMCA length as measured with IVUS was 7.37 ± 4.2 mm and mean lumen area (LA) was 15.63 ± 4.76 mm 2 corresponding to a mean lumen diameter (LD) of 4.41 ± 0.67 mm. An IVUS derived mean LD of >4 mm was present in 71.7%, >4.5 mm in 43% and > 5 mm in 19% of patients. LMCA mean LA was significantly smaller in women as compared to men (14.1 ± 4.1 mm 2 and 16.2 ± 4.8 mm 2, P < 0.01). Multivariable analysis identified weight of the patient as the sole significant predictor for LMCA length while height of the patient and LMCA length were predictors of LMCA mean LA. Correlation coefficients of determination for all independent predictors were low ( R 2 < 0.1 for all). Conclusion: This study demonstrated that the mean LD of a non‐obstructive LMCA is 4 mm or greater in the majority of patients, with a mean LMCA length of 7.4 mm. Women have smaller luminal dimension than men. No clinically relevant predictors were found for both LMCA length and mean LA.